Desain Sistem Informasi Pengolahan Data Stok Air Minum Dalam Kemasan Pada Pt.Amia Batusangkar - daus, Firdaus (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
After conducting research at PT. Amanah Insanillahia Batusangkar found problems regarding the transaction process where the recording is still using Microsoft Excel on a standard basis. This has resulted in reports that are not accurate and precise. Inventory of goods using First In First Out (FIFO) can be controlled more and can know the total inventory costs that exist at any time without having to do the first physical calculation. The results of this study are a design information system inventory data on bottled drinking water stock at PT. AMIA Batusangkar uses the First In First Out (FIFO) method. By utilizing a computerized system is expected to help the decision-making process and by utilizing the PHP programming language as a software and MySQL database, this application can help less effective and efficient ways and can facilitate the making of results reports and decision making.